PENGARUH DESTINATION IMAGE TERHADAP REVISIT INTENTION MELALUI MEMORABLE TOURISM EXPERIENCE DAN TOURIST ENGAGEMENT WISATAWAN TRANS STUDIO DI KOTA BANDUNG - Gina Melati Ramdini; Abdul Ahmad Hafidh Nurmansyah (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the influence of destination image on revisit intention through memorable tourism experience and tourist engagement of Trans Studio Bandung tourists. The population of this study is male and female tourists living in the city of Bandung with a convenience sampling method to collect samples. The respondents are tourists aged 17-64 years who have visited Trans Studio Bandung at least 1 time in the last 2 years. The number of samples used in this study was 120 respondents. Data was collected through google forms based on the Likert scale, and simple regression analysis, multiple, and sobel tests were carried out. The results of the study show that destination image has a positive effect on the memorable tourism experience. Destination image, and memorable tourism experience have a positive effect on tourist engagement. Revisit intention is influenced by destination image, memorable tourism experience, and tourist engagement. Memorable tourism experience is able to mediate the influence of destination image on tourist engagement and revisit intention. Tourist engagement mediates the influence of destination image and memorable tourism experience on revisit intention. This research is expected to be beneficial for further research, as well as provide important insights for the development of artificial tourism in increasing revisit intention.